The IκB Kinase Complex Is Required for Plexin-B-Mediated Activation of RhoA - Zielonka, Matthias (Public Library of Science, 2014)
Plexins are widely expressed transmembrane proteins that mediate the cellular effects of semaphorins. The molecular mechanisms of plexin-mediated signal transduction are still poorly understood. Here we show that signalling via B-family plexins leading to the activation of the small GTPase RhoA requires activation of the IκB kinase (IKK)-complex. In contrast, plexin-B-dependent regulation of R-Ras activity is not affected by IKK activity. This regulation of plexin signalling depends on the kinase activity of the IKK-complex, but is independent of NF-κB activation. We confirm that the IKK-complex is active in tumour cells and osteoblasts, and we demonstrate that plexin-B-dependent tumour cell invasiveness and regulation of osteoblast differentiation require an active IKK-complex. This study identifies a novel, NF-κB-independent function of the IKK-complex and shows that IKK directs plexin-B signalling to the activation of RhoA.